Critical Geography and Teaching Against Neoliberal Racial Capitalism in New York City Elementary Schools - Sonu, Debbie; Zaino, Karen; Helfenbein, Robert J. (Critical Education, 2025)
What might an anti-capitalist education look like? To address this question, we examine the curricular visions of 56 elementary school teachers in New York City, who were asked to design one lesson on the issue of social class and economic inequality. Grounded in neoliberal racial capitalism and critical geography, our analysis finds that teachers who emphasize specific places -- whether schools, city environments, the national context, or global landscapes – are better able to orient their teaching toward explicitly critical and systemic analyses of economic inequality and its constitutive links to race, gender, and other socio-political hierarchies. Their lessons demonstrate how teaching can disrupt the neoliberal over-reliance on the individual consumer typically found in financial literacy schemes. A presentation of their lessons, seldom found in the existing literature, is followed by a discussion of what a multi-scalar approach to economic inequality can offer to the field of research, teacher education, and teaching.